Developing Children with Special Needs Through Love, Understanding and Rationality. - Samitasiri, Nipa (European Journal of Sustainable Development, 2016)
Children with Special Needs refers to a specific group of children and youngsters who require additional assistance due to their physical, mental and/or intellectual disabilities and limited physical development. And Special Educational Need: SEN is one of their usual requirements. Additional assistance is to be given to those with impaired visibility, impaired audibility, Short Attention Disorder and multiple disabilities. Special Needs refers to additional support and assistance specifically given to this group of youth by surrounding people such as their family members, their teachers and classmates at school. So they can perform their daily tasks and pursue their studies like everyone else. To state an example, Ramkamhaeng University students with impaired audibility have shown improvement in their studies after participating in science-based activities: creating scientific picture frames. Engaged in social activities, they have more social interaction and communication with their classmates and teachers. They have become more supportive for one another. And due of the moral and academic support they mutually get, they perform better in class. Some even got an academic honour. Offering additional assistance to these youngsters is important and the family and society shall be fully aware. For the parents, choosing a right school for them is one of the priorities. The school should provide proper education and care with the suitable teaching and learning approaches in order to encourage their development and progress. Teachers also play an important role in assisting and resolving problems. They should understand each individual’s nature so that they can adjust their teaching methods and techniques to motivate the student to learn. Teachers should also be sensitive and attentive to students’ requirements and limitations. Students should be encouraged to do what they are good at so they can be proud and think positively about themselves. This will encourage them to live happily in the society, not feeling they are a burden to other people. Key Words: Children with Special Needs, Developing Children with Special Needs